Detection of Single-Copy Sequences with Digoxigenin-Labeled Probes in a Complex Plant Genome After Separation on Pulsed-Field Gels - T. Lahaye; B. Rueger; S. Toepsch; J. Thalhammer; P. Schulze-Lefert (BioTechniques)
In recent years, the application of rare cutting restriction enzymes, the separation of resulting DNA fragments on pulsed-field gels and the subsequent Southern blot analysis using radioactively labeled probes have been standard laboratory methods to create long-range physical maps of complex genomes. The disadvantages of this technology are the hazardous handling risks when working with radioactivity and long exposure times. In this paper, we describe the use of nonradioactively labeled probes for single-copy sequence detection in a complex plant genome after pulsed-field electrophoretic separation of DNA fragments in the Mbp range. The approach avoids the use of radioactivity and also reduces the exposure time from one to seven days to approximately 2–3 h.